2015
DOI: 10.15517/rbt.v46i2.19527
|View full text |Cite
|
Sign up to set email alerts
|

Composición y distribución de la ictiofauna en la Laguna del Mar Muerto, Pacífico mexicano

Abstract: La Laguna del Mar Muerto, Oaxaca-Chiapas fue muestreada entre 1991 y 1993 con el objetivo de caracterizar la ictiofauna en cuanto a su composición y abundancia. Se colectaron un total de 27 971 peces que aportaron 120.9 kg. La ictiofauna de la región está caracterizada por 29 familias, 45 géneros y 66 especies. El mayor número de especies se presenta en la parte sureste de la laguna (cerca de la Boca de Tonalá), área con mayor influencia marina, abundante vegetación costera y mayor descarga fluvial. El menor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The dominance of the families Sciaenidae and Carangidae is consistent with studies in Mexico (Tapia-García et al , 1995; Amezcua-Linares, 1996), which noted the dominance in diversity, frequency and abundance of these families. Nevertheless, the numerical dominance of Porichthys margaritatus , Pontinus sp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The dominance of the families Sciaenidae and Carangidae is consistent with studies in Mexico (Tapia-García et al , 1995; Amezcua-Linares, 1996), which noted the dominance in diversity, frequency and abundance of these families. Nevertheless, the numerical dominance of Porichthys margaritatus , Pontinus sp.…”
Section: Discussionsupporting
confidence: 90%
“…The 148 species recorded in this study are fewer than previously reported for other latitudes of the TEP that used similar sampling gears. Northward, in the Central Pacific of Mexico (off Nayarit, Michoacán and Guerrero), 215 fish species have been recorded (Amezcua-Linares, 1996) and off the coast of the Gulf of Tehuantepec (off Oaxaca and Chiapas) 166 species have been reported (Tapia-García et al , 1995). According to Robertson & Cramer (2009), species-richness peaks at the centre of the Panamic Province (Costa Rica and Panamá), but is fairly high throughout most of the mainland of the TEP, except in the northern part of the Gulf of California and in the Sinaloan and Central American Gap, including the coast of El Salvador, where species richness was significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…However, in estuarine wetlands, cast nets are highly effective for achieving broad taxonomic representation in several shallow habitats and accurate estimates of abundances (Sheaves & Johnston 2009). Other published lists correspond to Mar Muerto (66 species; Tapia- García et al 1998), Oriental-Occidental (72 species ;Chávez 1979) and Superior-Inferior lagoon systems (47 species; Tapia- García & Mendoza-Rodríguez 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of ichthyofaunal similarity between seven lagoon systems of the GT (Superior-Inferior, Oriental-Occidental, and Mar Muerto in addition to LJB, PSD, CPE, and CHP) was examined with the Jaccard index on a matrix of presence/absence of species based on the information described here and in the inventories published by Chávez (1979), Tapia- García et al (1998), Tapia- García & Mendoza-Rodríguez (2005) and Gómez-González et al (2012). The classification was by the UPGMA method, and the identification of groups in the dendrogram was performed with a test of similarity profiles (SIMPROF, 1000 permutations, and 999 simulations) at a significance level of α = 0.05.…”
Section: Regional-scale Analysismentioning
confidence: 99%
See 1 more Smart Citation